Relationship Between Self-esteem, Anxiety and Mathematical Motivation in Precalculus Students - Castro Méndez, Didier Alberto (2024)
This research was focused on exploring the relationship between self-esteem, anxiety and mathematical motivation in precalculus students of the Metropolitan Campus of the Latin American University of Science and Technology (ULACIT in Spanish), during the first quarter of 2024. Possible differences in terms of gender and area of study were analyzed for each of the variables. The methodological approach adopted was of a quantitative descriptive-correlational nature. The sample consisted of 374 pre-calculus students. To carry out the analysis of the hypotheses proposed, Student’s t and Pearson’s correlation statistical techniques were used. The findings revealed that males showed higher levels of anxiety and lower motivation towards mathematics than females. No significant differences in anxiety, mathematical motivation, and self-esteem were identified according to the area of study. A correlation was observed between the variables: as mathematics anxiety decreased, self-esteem and motivation towards the subject increased. In addition, an increment in mathematical motivation was related to an increase in self-esteem. The study showed that 22.46% of the students presented high levels of mathematical anxiety, while more than 55% showed high levels of self-esteem and mathematical motivation.